Diet and gender in the Tiwanaku colonies: Stable isotope analysis of human bone collagen and apatite from Moquegua, Peru. Issue 3 (14th July 2015) - Somerville, Andrew D.; Goldstein, Paul S.; Baitzel, Sarah I.; Bruwelheide, Karin L.; Dahlstedt, Allisen C.; Yzurdiaga, Linda; Raubenheimer, Sarah; Knudson, Kelly J.; Schoeninger, Margaret J.
ABSTRACT Objectives: Gender and other facets of social identity play important roles in the organization of complex societies. This study reconstructs dietary practices within the Middle Horizon (AD 500–1000) Tiwanaku colonies in southern Peru to increase our knowledge of gendered patterns of consumption within this early expansive state. Methods: We use stable isotope analysis of 43 human bone samples representing 14 females, 20 males, 8 juveniles, and 1 indeterminate individual recovered from burial excavations at the sites of Rio Muerto and Omo in the Moquegua Valley. Data are contextualized by comparisons with previously published Tiwanaku isotope data from the period. Results: Our results find mean values of δ13Capatite = −7.3 ± 1.6% (N = 36, 1SD), δ13Ccollagen = −12.3 ± 1.5% (N = 43, 1SD), and δ15Ncollagen = 8.4 ± 1.6% (N = 43, 1SD). Between the sexes, Mann‐Whitney U tests demonstrate significant differences in δ13Ccollagen (U = 74, P = 0.021), but no differences in δ13Capatite (U = 58, P = 0.095) or δ15Ncollagen (U = 116, P = 0.755) values. Conclusions: These data indicate relatively high C4 plant consumption among the Tiwanaku colonies, and support paleobotanical and archaeological evidence that maize (Zea mays) was the staple crop. Dietary values are similar overall between the sexes, but significantly higher δ13Ccollagen values in males is consistent with a model of gendered norms of consumption similar to that of the later Inca (AD 1438–1533), where males consumed more maize than females, often in the form of beer (chicha). Results provide new insights on social dynamics within the Tiwanaku colonies and suggest the increased importance maize consumption for males during the Tiwanaku expansion. Am J Phys Anthropol 158:408–422, 2015. © 2015 Wiley Periodicals, Inc.